GAMBARAN KEPERCAYAAN (TRUST) SANTRI PADA PEMBINA PONDOK PESANTREN - Fathul Lubabin Nuqul; Ardana Reswari Miranda Ningrum; Nur Hayati (RAHMATAN LIL ALAMIN: JOURNAL OF PEACE EDUCATION AND ISLAMIC STUDIES, 2019)
Islamic boarding schools are the backbone of Islamic education in Indonesia as a source that has not yet been explored. Islamic boarding schools have three elements, namely kyai, santri, and hut, as a place to live. The existence of clerics as an important figure in education in Islamic boarding schools is central. However, on the other hand, along with the expansion of the role of clerics in the community and the increasing quantity of santri in Islamic boarding schools. The role of clerics or coaches as an extension of the clerics' hands also determines the success of education in the hurricane. The relation between the santri and the coach is interesting to examine in this case, the santri trust in the coach. This research involved 212 santri from Islamic boarding schools in Jombang and Pasuruan. The measurement uses adaptation from leader to leader. This scale has four components, namely. 1) Benevolent; 2) Predictivity; 3) Integrity; and 4) Competence. This scale has good reliability, namely Î± = 0.915, while the power difference between 0.328-0.759. The results show that generally, santri have a pretty good belief in their supervisors. The research also shows that santri generally believe that their behavior and actions can be predicted, or consistent. On the other hand, for the integrity component of the coach, the santri does not trust. The result implies the exemplary aspects and beliefs of santri towards their education in Islamic boarding schools.